Maternal buprenorphine treatment and infant outcome. (1st November 2017) - Jansson, Lauren M.; Velez, Martha L.; McConnell, Krystle; Spencer, Nancy; Tuten, Michelle; Jones, Hendree; Rios, Rebeca; King, Van L.; Gandotra, Neeraj; Millio, Lorraine; DiPietro, Janet A.
Highlights: Study focused on a sample of buprenorphine-exposed infants. Maternal gestational buprenorphine dose is a positive predictor of NAS severity. Polysubstance exposure most potently predicted NAS severity. Findings underscore the need for comprehensive addictions treatment during pregnancy. Abstract: Background and objectives: Maternal buprenorphine maintenance predisposes the infant to exhibit neonatal abstinence syndrome (NAS), but there is insufficient published information regarding the nature of NAS and factors that contribute to its severity in buprenorphine-exposed infants. Methods: The present study evaluated forty-one infants of buprenorphine-maintained women in comprehensive substance use disorder treatment who participated in an open-label study examining the effects of maternal buprenorphine maintenance on infant outcomes. Modifiers of the infant outcomes, including maternal treatment and substance use disorder parameters, were also evaluated. Results: Fifty-nine percent of offspring exhibited NAS that required pharmacologic management. Both maternal buprenorphine dose as well as prenatal polysubstance exposure to illicit substance use/licit substance misuse were independently associated with NAS expression. Polysubstance exposure was associated with more severe NAS expression after controlling for the effects of buprenorphine dose. Other exposures, including cigarette smoking and SRI use, were not related to outcomes. Maternal buprenorphine dose was positively associated with lower birth weight and length. Conclusions: Polysubstance exposure was the most potent predictor of NAS severity in this sample of buprenorphine-exposed neonates. This finding suggests the need for interventions that reduce maternal polysubstance use during medication assisted treatment for opioid use disorder, and highlights the necessity of a comprehensive approach, beyond buprenorphine treatment alone, for the optimal care for pregnant women with opioid use disorders.